EFFECT OF TEENAGE PREGNANCY ON ACADEMIC PERFORMANCE OF STUDENTS IN MASAFU TOWN COUNCIL IN BUSIA DISTRICT - MUKHWANA GERALD B_BSWASA_2024.pdf (My University, 2024)
The purpose of the study was to investigate the effect of teenage pregnancy on academic performance among students in Masafu Town Council, Busia District. Utilizing a sample of 63 respondents from a total of 75, and employing a cross-sectional survey design, the study aimed to determine the impact of pregnancy rate, access to healthcare, and socioeconomic status on academic performance. The findings revealed that while teenage pregnancy introduced significant challenges for students, including interruptions in their educational pursuits and difficulties in balancing school responsibilities, its direct impact on academic performance was minimal. The study concluded that although factors such as healthcare access and socioeconomic status played roles in influencing academic outcomes, the effects were not strongly correlated. Based on these findings, the study recommended implementing targeted support systems, including enhanced healthcare services and educational support programs for teenage mothers, to better address the challenges they face and improve their academic performance. The study also suggested further research to explore additional variables and contextual factors that might influence the relationship between teenage pregnancy and educational outcomes.